2012
DOI: 10.1002/ejic.201200440
|View full text |Cite
|
Sign up to set email alerts
|

Chromate‐Mediated One‐Step Quantitative Transformation of PW12 into P2W20 Polyoxometalates

Abstract: Polyoxometalates have been at the frontiers of science since the discovery of Keggin-type polyoxometalates (POMs) about a century ago. Today these polyoxometalates are still of major scientific interest, not only due to their wide range of applications [1][2][3][4][5][6][7][8][9][10][11][12] in analytical chemistry, in life sciences, as homo-and heterogeneous catalysts, as essential building blocks for the design of photoactive complexes, and hybrid organic/inorganic materials, but also from purely synthetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…e chromate anions are recovered by adding stoichiometric amounts of KOH solution to the Cr(VI) solution to yield potassium chromate powder after solvent evaporation (Figure 15). is is in agreement with the proposed reaction pathway of PW 10 Cr 2 (aq) species [22]. Most importantly, we are able to isolate this intermediate species.…”
Section: Journal Of Chemistrysupporting
confidence: 91%
See 1 more Smart Citation
“…e chromate anions are recovered by adding stoichiometric amounts of KOH solution to the Cr(VI) solution to yield potassium chromate powder after solvent evaporation (Figure 15). is is in agreement with the proposed reaction pathway of PW 10 Cr 2 (aq) species [22]. Most importantly, we are able to isolate this intermediate species.…”
Section: Journal Of Chemistrysupporting
confidence: 91%
“…Polyoxometalates (POMs) are a class of discrete anionic metal oxides of groups 5 and 6 and POMs exhibit attractive properties such as thermal and oxidative stability, remarkable electronic and magnetic properties, and Brønsted acidity, which result in intriguing applications ranging from medicine, catalysis to material science [18][19][20][21]. Recently, it was reported that the slow addition of H 3 PW 12 O 40 to an aqueous solution of K 2 CrO 4 at room temperature (pH � 6.6 ± 0.2) led to the formation of the final product K 14 [P 2 W 20 O 72 ]•24H 2 O (denoted as P 2 W 20 ) [22]. It was proposed that a Cr(VI)-stabilized [PW 10 O 36 (CrO 4 ) 2 ] 9− intermediate was formed, which played a significant role in the formation of the P 2 W 20 cluster.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ion-association, hydrolysis, and condensation reactions that lead to self-assembly of clusters into materials are at the heart of virtually all synthetic and natural aqueous inorganic processes. Thus observing these processes directly in solution by methods such as small-angle X-ray scattering (SAXS) can provide valuable insight into fundamental aqueous ion behaviors that control crystallization, dissolution, transport, ion-exchange, and adsorption and desorption at interfaces. Yet the inorganic scientific community is only beginning to use this technique to full advantage. , …”
Section: Introductionmentioning
confidence: 99%